A Comparative Analysis of Modernist Islamic Thought on the Decline and Revival of the Muslim World: Rashid Rida, Malik Binnabi, Amir Shakib Arslan, and Abul Hasan Al-Nadwi - Moh Al Ahyar; Faris Ahsanu Ibadillah; Muhammed Siddiq (PT PUSTAKA CENDEKIA GROUP, 2026)
This article analyzes and compares the thinking of four prominent modern Islamic intellectuals on the causes of Muslim decline and the pathways to revival: Muhammad Rashid Rida through Majallah Al-Manar, Amir Shakib Arslan in Limadza Ta'akhkhara al-Muslimun, Malik Binnabi in Shurut al-Nahdha, and Abul Hasan Ali al-Nadwi in Madha Khasira al-'Alam bi Inhitat al-Muslimin. Employing a comparative-analytical method, this study finds that all four thinkers converge on the necessity of fundamental reform and a return to authentic Islamic values, yet diverge in their emphases: Rida stresses theological reform and ijtihad; Arslan foregrounds practical political action; Binnabi develops a sociological analysis of civilizational pathology; and al-Nadwi highlights the losses suffered by humanity at large as a consequence of Muslim decline and the abdication of Islam's role as moral leadership for mankind. The convergences and divergences among these four thinkers constitute a rich and uniquely complementary intellectual map of modern Islam.